La Danza como lenguaje transformador en el ejercicio artístico pedagógico del maestro Hilmer Ramos (2021)
The art of dance contributes to the integral development of human beings. Through it they learn to use their body as a means of expression, highlighting a culture that is often forgotten or mistreated due to ignorance. This degree work seeks to highlight the influence that the practice of dance as a transformative language has had on the artistic and pedagogical exercise of teacher Hilmer Ramos, together with the people who have been linked to the training actions offered by the teacher through the different routines, which have been accompanied by discipline and dedication, generating in the apprentices appropriation of the dance to cultivate a future artistic professional being a reference for the new generations.